First aid counseling for sports injuries among junior high school students in Sidoarjo district - Andriana, Laily Mita; Billy Emir Rizkanto; Muhamad Fauzi Antoni; Afif Dwi Nugraha; Shery Iris Zalillah; Ika Jayadi (Kanigara, 2025)
This community service aims to increase the knowledge of junior high school students in Sidoarjo Regency about first aid in sports injuries. Counseling is carried out through interactive lecture methods, practical demonstrations, and question and answer sessions that actively involve students. The material presented included the types of sports injuries, correct first aid steps, and injury prevention through heating and cooling techniques. The results of the evaluation showed that as many as 80% of students experienced a significant improvement in their understanding, as measured through a comparison of pre-test and post-test results. This activity has succeeded in having a positive impact in raising students' awareness of the importance of first aid as well as preparing them to handle emergency situations related to sports injuries.